Recent Advances in Chemical Modification of Peptide Nucleic Acids - Rozners, Eriks (Journal of Nucleic Acids, 2012)
Peptide nucleic acid (PNA) has become an extremely powerful tool in chemistry and biology. Although PNA recognizes single-stranded nucleic acids with exceptionally high affinity and sequence selectivity, there is considerable ongoing effort to further improve properties of PNA for both fundamental science and practical applications. The present paper discusses selected recent studies that improve on cellular uptake and binding of PNA to double-stranded DNA and RNA. The focus is on chemical modifications of PNA's backbone and heterocyclic nucleobases. The paper selects representative recent studies and does not attempt to provide comprehensive coverage of the broad and vibrant field of PNA modification.